2017
DOI: 10.1007/s10741-017-9598-3
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure in the elderly: ten peculiar management considerations

Abstract: Chronic heart failure (HF) is a disease with significantly higher prevalence in the elderly or patients older than 65 years old. Typically, older patients have more risk factors for HF, more comorbidities, and are more likely to have recurrent admissions for acute decompensations. With HF burden on health care systems primarily related to hospital and nursing home costs, it is critical that elderly patients are approached with a clear understanding of certain unique clinical, laboratory, imaging, and pharmacok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…van Almen et al found that miR-18 and miR-19 levels were decreased in an aged HF-prone mouse strain when compared to age-matched controls (58, 59). These findings were also confirmed in human samples, and this is crucial since HF is a frequent comorbidity in elderly patients (58, 60). …”
Section: Mirnas In Cardiovascular Agingsupporting
confidence: 57%
“…van Almen et al found that miR-18 and miR-19 levels were decreased in an aged HF-prone mouse strain when compared to age-matched controls (58, 59). These findings were also confirmed in human samples, and this is crucial since HF is a frequent comorbidity in elderly patients (58, 60). …”
Section: Mirnas In Cardiovascular Agingsupporting
confidence: 57%
“…Nonetheless, the optimal use of biomarkers for risk stratification is controversial, also because several aspects have not been specifically analysed, including the influence of age on some HF biomarkers, and the need for age-specific cut-offs for risk prediction. 2,3 In both healthy subjects and HF patients, circulating levels of B-type natriuretic peptides are significantly influenced by age, as well as by cardiovascular (e.g. atrial fibrillation) and non-cardiovascular conditions [such as anaemia and chronic kidney disease (CKD)], whose prevalence increases with age.…”
Section: Introductionmentioning
confidence: 99%
“…These factors contribute to late diagnosis, thus making complementary exams important (Figure 1). 175 The use of biomarkers, such as outpatient values of brain natriuretic peptide (BNP) below 35 ng/mL, excludes the presence of HF in symptomatic individuals. In individuals with acute dyspnea in the emergency room, however, BNP values over 250 ng/mL or pro-BNP over 1,800 ng/mL indicate HF as the cause of the symptoms.…”
Section: Heart Failurementioning
confidence: 99%